THE PSYCHOLOGICAL STRUCTURE OF HUMOUR AS A COMPONENT OF LUDIC COMPETENCE (THE SUMMATIVE ASSESSMENT) - Kobzieva, Iuliia (PSYCHOLOGICAL JOURNAL, 2020)
The article is devoted to the empirical study of humor as a component of game competence. A set of psycho-diagnostic methods which include the author's methodology for diagnosing game competence based on the mentioned humor development criteria including ludic competence, potentially beneficial humor styles, emotional intelligence, coping strategies, self-actualization, psychological well-being, actual abilities, has been designed.The use of groups of indicators and a set of methods created on their basis to study the peculiarities of the development of humor revealed at the ascertaining stage of the study the factor structure of humor, which is represented by three factors: Communicative Perceptiveness ”. As multiple linear regression analysis showed, among humor development predictors being simultaneously its assessment criteria were “Self-Acceptance” and “Human as an Open System” as markers of psychological well-being and “Self-Enhancing Humor” as a marker of beneficial humor style. A correlation analysis of the links between humor as a component of ludic competence and its concrete indices made it possible to conclude that humor as a component of ludic competence represents a personality's capacity to shift the perception of life challenges through forming their integral perception of positive and negative aspects. Next, humor is a means of self-preservation, and psychological defense against unfavorable factors. This provides an individual with the ability to cope with stress, self-development under the condition of combining affiliative and self-supporting humor that underlies a “reliance on the best, the most healthy-in-oneself” strategy.According to its psychological content, humor as a component of game competence is aimed at: 1) maintaining a humorous, easy, fun, ironic or self-ironic attitude to life events, to the environment, to himself in a variety of situations; 2) identify contradictions or inconsistencies in the behavior of other people, focusing on something positive, even in difficult, problematic life situations and circumstances - in order to cope with them, to overcome these circumstances; 3) use humor as a means of learning, especially yourself, development opportunities, as well as others.